2020
DOI: 10.1155/2020/7590207
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Smoking on COVID-19 Symptom Severity: Systematic Review and Meta-Analysis

Abstract: Background. Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SAR2-COV-2) and was first identified in Wuhan, China, in December of 2019, but quickly spread to the rest of the world, causing a pandemic. While some studies have found no link between smoking status and severe COVID-19, others demonstrated a significant one. The present study aimed to determine the relationship between smoking and clinical COVID-19 severity via a systematic meta-analysis approach. Me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 47 publications
(48 reference statements)
2
78
2
2
Order By: Relevance
“…Immunity system is weaker in male than in female sex, therefore men are at higher risk of viral infection than women [22]. Because the low prevalence of smoking in patients hospitalized with COVID-19 [23,24], the protective effect of tobacco is largely discussed [25]; however, several meta-analyses of observational studies have confirmed that smoking habit is related to severe COVID-19 and adverse outcomes [19,21,[26][27][28]. Tobacco smoking is associated with upregulation of the angiotensin-converting-enzyme-2 (ACE2), immune system disturbance, endothelial injury and hypercoagulable state [28,29]; these factors and pre-existing comorbidities could explain adverse outcomes observed in smokers with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Immunity system is weaker in male than in female sex, therefore men are at higher risk of viral infection than women [22]. Because the low prevalence of smoking in patients hospitalized with COVID-19 [23,24], the protective effect of tobacco is largely discussed [25]; however, several meta-analyses of observational studies have confirmed that smoking habit is related to severe COVID-19 and adverse outcomes [19,21,[26][27][28]. Tobacco smoking is associated with upregulation of the angiotensin-converting-enzyme-2 (ACE2), immune system disturbance, endothelial injury and hypercoagulable state [28,29]; these factors and pre-existing comorbidities could explain adverse outcomes observed in smokers with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies reported smoking history instead of current smoking, which might include former smokers and therefore underestimate current smoking status among COVID-19 patients 70 . Second, former smokers have longer exposure period or accompanying diseases such as asthma, COPD due to smoking 18 . As a result, former smoking showed higher risk of negative outcomes compared with current smoking.…”
Section: Publication Bias Of Included Studiesmentioning
confidence: 99%
“…The differences between risk of severity and death between former and never smoker COVID-19 patients have not been shown [11][12][13] . Because of small sample sizes included in these previous studies and differing definitions of disease severity, existing systematic reviews and meta-analyses found limited evidence suggesting that the risk of COVID-19 infection maybe lower among smokers compared to non-smokers, albeit from highly heterogeneous studies [14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…This elevated expression occurs through activation of the α7 subtype of the nicotine acetylcholine receptor (α7-nAChR) ( 80 ). This is further highlighted in a recent meta-analysis revealing that patients with a history of smoking, as well as active smokers, recorded a significant severity of COVID-19 ( 81 ). In fact, cigarette smoking promotes alterations in the respiratory tract that might increase the risk of viral infections through multiple mechanisms such as impairment of mucociliary clearance, mucus hypersecretion, fibrosis, and dysfunction of the epithelial barrier.…”
Section: Differential Response To Covid-19 Could Be Related To Ace2 Ementioning
confidence: 88%